Optimal Design of Failure-Censored Constant-Stress Life Test Plans for the Inverse Weibull Distribution - Ismaila, Ali A.; Tamimi, A. Al (Проблемы прочности, 2019)
This paper presents the optimal design of constant-stress partially accelerated life tests (CSPALT) using type-II censored data from the inverse Weibull distribution. The maximum likelihood approach is applied to estimate the distribution parameters and the corresponding factor. In addition, the corresponding confidence interval estimates are obtained. Moreover, optimal CSPALT plans are developed using the D-optimality criterion. That is, the proportion of test units that should be allocated to run under accelerated condition is optimally determined. This proportion is obtained such that the generalized asymptotic variance of the maximum likelihood estimators of the model parameters is minimized. To illustrate the theoretical results presented in this paper, simulation studies are conducted. Предложена модель ускоренных ресурсных испытаний при постоянном напряжении с использованием данных, подвергнутых цензурированию типа II с обратным распределением Вейбулла. С помощью метода максимального правдоподобия определены параметры распределения и коэффициента ускорения. Выполнены оценка соответствующего доверительного интервала и оптимизация ускоренных ресурсных испытаний при постоянном напряжении по D-критерию оптимальности. При этом выборка части программы нагружения для ускоренных ресурсных испытаний оптимизируется таким образом, чтобы минимизировать обобщенную асимптотическую дисперсию показателей максимальной вероятности. Работоспособность предложенного подхода показана на тестовом примере. Запропоновано модель прискорених ресурсних випробувань при постійній напрузі з використанням даних, підданих цензурування типу II із зворотним розподілом Вейбулла. За допомогою методу максимальної правдоподібності визначені параметри разподілу і коефіцієнта прискорення. Виконано оцінка відповідного довірчого інтервалу і оптимізація прискорених ресурсних випробувань при постійній напрузі по D-критерієм оптимальності. При цьому вибірка частини програми навантаження для прискорених ресурсних випробувань оптимізується таким чином, щоб мінімізувати узагальнену асимптотичну дисперсію показників максимальної ймовірності. Працездатність запропонованого підходу показана на тестовому прикладі.